Sistema Informático de Facturación de citas y detalle de tratamientos médicos en el Hospital del Día "Gabriel Andrade" del Cantón Ventanas. - Mejía Guanoluisa, Kevin Jim (2019)
Technology is currently advancing very fast, and it is very common for most companies to want to automate their processes, to reduce customer service time and improve the quality of the services they offer. That's why technology is very important nowadays. The Hospital of the Day "Gabriel Andrade" located in the Canton of Ventanas, province of Los Ríos, does not want to be left behind, since it is desired to develop a computerized system of Billing of appointments and details of medical treatments, so that patients notify them by email and SMS messages, all the incidents that occur in the aforementioned health center. The present project has been carried out in order to develop a system, which will help in a systematized way to a private health entity. The idea of ​​this project comes from generating billing of the medical treatments that are carried out in the Hospital of the Day "Gabriel Andrade", where it tries to take a truthful and precise control of economy of the clinic, giving confidence, speed and security and thus to be able to improve the service of the hospital. The software will facilitate the administrative work, thus being able to provide better quality of service, and at the same time that both officials and beneficiaries will generate compliance. This project aims to solve common problems when giving an invoice. This prototype will allow access to the information of all authorized doctors in a quick, easy and timely manner of the aforementioned clinic.